PEMBUATAN WEB MARTABAK BANGKA QUM MENGGUNAKAN PHP DAN MYSQL - Kuwat Setiyanto; Yoga Aprianto (Asosiasi Dosen Muda Indonesia, 2024)
Creating the Bangka QUM Martabak Web using PHP and MySQL as an effort to utilize technology to increase efficiency and convenience in the online martabak ordering process. This research includes developing a website that is integrated with a MySQL database to store and manage ordering information. Customers can explore the martabak menu, select the desired variant, and complete the ordering process easily. In the development process, the PHP programming method is used to design a responsive and dynamic user interface. A MySQL database is used to store order information, including customer details, type of martabak selected, and order status, enabling efficient management and tracking of order history. The Martabak Bangka QUM website aims to provide a pleasant and practical shopping experience for customers. With the online ordering system, it is hoped that it can increase business competitiveness and provide added value in providing better service to customers.